2017
DOI: 10.1002/jcad.12153
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Life Transition on Emerging Adult Attachment, Social Support, and Well‐Being: A Multiple‐Group Comparison

Abstract: Life transitions can induce distress for emerging adults. This study compared a model of the attachment, social support, and well‐being of emerging adults in transition with a model of those not in transition (N = 378). The transition sample reported less life satisfaction and environmental mastery and higher attachment avoidance than the nontransition sample. The transition sample showed weaker mediating effects of social support, suggesting that attachment accounted for additional unique variance for this gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
(84 reference statements)
0
15
0
4
Order By: Relevance
“…Although, not all emerging adults experience difficulties during the transitions typical of this stage of life, life transitions can generate distress for emerging adults [ 10 ], and the distress accompanying such transitions poses a considerable threat to the well-being of the emerging adults [ 7 ]. Epidemiological research and population surveys have concluded that women report higher psychological distress that men [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], although such differences vary according to socioeconomic variables, historical and contextual factors [ 15 , 16 , 17 , 18 ], and age [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although, not all emerging adults experience difficulties during the transitions typical of this stage of life, life transitions can generate distress for emerging adults [ 10 ], and the distress accompanying such transitions poses a considerable threat to the well-being of the emerging adults [ 7 ]. Epidemiological research and population surveys have concluded that women report higher psychological distress that men [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], although such differences vary according to socioeconomic variables, historical and contextual factors [ 15 , 16 , 17 , 18 ], and age [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Les transitions normatives sont celles attendues socialement ou biologiquement, telles que la puberté ou la parentalité (Bronfenbrenner, 1986). Elles vont être rencontrées par tout individu au cours de sa vie et vont poser des défis psychologiques transitoires (e.g., Lane, Leibert, & Goka-Dubose, 2017). À l'inverse, les transitions non-normatives sont des transitions qui surviennent de manière inattendue comme le divorce ou la maladie (Bronfenbrenner, 1986).…”
Section: Période De Transition Vers L'âge Adulteunclassified
“…En ce qui concerne le bien-être psychologique, de manière générale les individus rapportant un haut niveau de sécurité d'attachement présentent un haut niveau de bien-être (Love et al, 2009 ;Ryan et al, 2016). Lors de périodes de transition, seul un attachement de style anxieux est négativement lié au bien-être psychologique (Lane et al, 2017).…”
Section: Ajustement Psychosocial Et Styles D'attachementunclassified
“…Depressive and anxiety symptoms have been found to develop as early as the first weeks of college (Andrews & Wilding, 2004;Moreira & Telzer, 2015), and loneliness also increases shortly after the college transition (Cutrona, 1982;Shaver et al, 1985). Furthermore, satisfaction with life often decreases during times of stress and transition in emerging adulthood (Denovan & Macaskill, 2017;Lane, Leibert, & Goka-Dubose, 2017), thus it is likely that the college transition may cause a dip in life satisfaction. Personal characteristics such as shyness may directly increase the risk for poorer adjustment during this time.…”
Section: Individual and Interpersonal Environment Effects On Socioementioning
confidence: 99%